6 - Party identification and service delivery protests in the Eastern Cape and Northern Cape, South Africa - Sethulego Matebesi,; Lucius Botes, (African Sociological Review, 2017)
Service delivery protests against municipalities in South Africa have become common. This article discusses the relationship between party identification and these protests. It presents an in-depth analysis of two qualitative case studies: one in the Eastern Cape Province, where protests have mainly been about the shortage and poor quality of housing, and one in the Northern Cape, where protests were mainly aimed at getting the mayor to resign. A widely held view in the social movement literature is that the stronger the identification with the ruling party the less likely people are to protest, even when they have cause to do so. In South Africa, the connection between party affiliation and social movement is blurred. We found that partisan protesters were consequently able to navigate successfully between the party and concerned residents’ groups. There is a pressing need to consider what norms and values these protests will transmit to future generations.